Microstructural Development in a TRIP-780 Steel Joined by Friction Stir Welding (FSW): Quantitative Evaluations and Comparisons with EBSD Predictions - Medina, Gladys Perez; Ferreira, Hugo Lopez; Robledo, Patricia Zambrano; Pérez, Argelia Miranda; Valdés, Felipe A. Reyes (2016)
The present work describes the effect of FSW on the result microstructure in the stir zone (SZ), thermo-mechanically affected zone (TMAZ), heat affected zone (HAZ) and base metal (BM) of a TRIP-780 steel. X-ray diffraction (XRD), optical microscopy (OM) and EBSD were used for determinations retained austenite (RA) in the SZ, It was found that the amount of RA developed in SZ was relatively large, (approximately 11% to 15%). In addition, recrystallization and the formation of a grain texture were resolved using EBSD. During FSW, the SZ experienced severe plastic deformation which lead to an increase in the temperature and consequently grain recrystallization. Moreover, it was found that the recrystallized grain structure and relatively high martensite levels developed in the SZ lead to a significant drop in the mechanical properties of the steel. In addition, microhardness profiles of the welded regions indicated that the hardness in both the SZ and TMAZ were relatively elevated confirming the development of martensite in these regions. In particular, to evaluate the mechanical strength of the weld, lap shear tensile test was conducted; exhibited the fracture zone in the SZ with shear fracture with uniformly distributed elongation shear dimples.